Tinjauan Evaluasi Kelayakan Finansal Bus Trans Metro Pekanbaru (Studi Kasus: Koridor I Pandau – Ramayana) - Andri Mahendra; Hendra Taufik; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pekanbaru is the capital city of Riau Province which located in the center of Sumatra Island has made the government has a vision and a mission to transform the city of Pekanbaru as a metropolitan city. There are a lot of public transport users in the city of Pekanbaru. Some of them use Trans Metro Pekanbaru. The current investment in transportation is something that very risky because it requires huge modal, it is important to analyze the financial feasibility and a Vehicle Operational Cost (VOC). While analyzing the financial aspects by calculating the net present value, benefit cost ratio, internal rate of return, payback period and also sensitivity analysis. As a result the operational vehicle`s cost was Rp. 3738.63/km while the result of analysis combination with 30% equity and 70% of loans has produced the total investment costs of TMP reached Rp. 21,502,524,300.00 with NPV of Rp.6.944.296.351,48. BCR of 1.19 and PBP for 5 years and 8 months (the period time of vehicles for 7 years). It can be concluded that the investment is financially viable so investment Trans Metro Pekanbaru deserve to be operationalized.Keywords : Trans Metro, Analysis of Financial, Sensitivity Analysis, Investment, Pekanbaru